Język a tożsamość. Język pierwszy, drugi i obcy a sukcesy i niepowodzenia szkolne - Komorowska, Hanna (Neofilolog, 2017)
The article investigates relationships between national/ ethnic identity and languages used in the school context. The impact of imposed, attributed, regained and selected identities on first and second language proficiency is analyzed on numerous examples drawn from the areas of history, literature and culture. Approaches to bi-and monolingualism and bi and monoculturalism are then presented with special emphasis on the role of stereotypes. Linguistic factors which influence success and failure are discussed vis-à-vis immigration and re-emigration. Attention is given to difficulties encountered by students using restricted L1 codes as well as to problems faced by pupils lacking proficiency in the language of schooling. Implications are sought for language education in the school system.